PENGARUH UKURAN UMBI DAN DOSIS KALIUM TERHADAP PERTUMBUHAN DAN HASIL PRODUKSI BAWANG MERAH (Allium ascalonicum L.) VARIETAS LEMBAH PALU - H.Y Uke,Henry Barus,Ichwan S. Madauna, Kalwia (AGROTEKBIS, 2015)
The objective of this research was to study the effect of tuber size and rates of K fertilizer on the growth and yield of shallot (var. Lembah Palu). The site of this research was in Guntarano village, Tanantovea  Sub District of Donggala District.  This research began from June 2013 to August 2013. A randomized block design was used in this research which used two factors namely tuber size  and rates of Kalium. The tuber size consisted of two levels, small tuber (U1= 1.7-2.3g tuber-1) and large tuber (U2= 2.4-3.0 g tuber-1). The K fertilizer consisted of four rates i.e. 100 kg ha-1 K2O  (K1), 150 kg ha-1 K2O (K2),  200 kg ha-1 K2O (K3), and 250 kg ha-1 K2O (K4). The research treatments were replicated three times. This research  showed that the tuber size significantly affected all growth and yield parameters except plant height. The large tubers resulted in better growth than the small tubers. While K rates showed significant effect on all growth and yield parameters except shoot numbers. The K fertilizer applied at the rate of 100 kg ha-1 and 250 kg ha-1 showed greater yield than the others. There was an interaction effects between tuber size and the rates of K fertilizer for all growth and  yield parameters, except leaf number, shoot number and tuber diameter. The small tuber size applied with 100 kg K ha-1 and the large tuber size applied with 250 kg K ha-1 vindicated greater growth and production of shallot plant (var. Lembah Palu).